PROFILE PULMONARY ENDURANCE AND ANTHROPOMETRY OF TAEKWONDO ATHLETES - Ida Melani; Syafaruddin Syafaruddin; Herri Yusfi (Universitas Negeri Medan, 2023)
This study aims to determine the results of cardiopulmonary endurance and anthropometry in the South Sumatra TPC taekwondo dojang athletes. This type of research is descriptive. The population of the study were TPC taekwondo athletes, totaling 30 athletes. The sample in this study was taken from the whole or total sampling, namely 30 athletes. The data analysis technique was processed with the percentage of data obtained, namely for the results of cardiopulmonary endurance athletes have an average cardiopulmonary endurance in the very good category, and for anthropometric results on body mass index have an average condition that is in the good category, for the circumference The athlete's upper arm circumference is in the good category, and the average athlete's abdominal circumference is in the good category. The implementation of this study is that if athletes have good cardio-pulmonary endurance and anthropometry, it will affect the results of sports achievements, especially in taekwondo sports.